Pengaruh Karakteristik Organisasional dan Individual terhadap Stres Kerja Perawat di Ruang Rawat Inap Rumah Sakit Royal Prima Medan - Christine Yennyanti; Sri Lestari Ramadhani Nasution; Ermi Girsang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Stress is a non-specific response, the process of individual psychological disruption that can interfere with him in carrying out his job. This study aims to determine the effect of organizational and individual characteristics on the work stress of nurses in the inpatient room of Royal Prima Medan Hospital in 2019. This type of research is quantative with design cros-sectional. The sampling technique used the formula to take 25% of the total population, namely 60 nurses. Data collection techniques using questionnaires and research interview instruments. Data analysis was using the chi spearmen test if the p value <0.05 and multivariate using logistic regression statistical tests. The results of the research on the effect of autonomy on the occurrence of work stress obtained the correlation coefficient of 0.850 and p-value of 0.002, the interaction of nurses with the correlation coefficient of 0.916 and p-value of 0.000, family support, the result of the correlation coefficient of 0.785 and p-value of 0.010, conflict with co-workers as the result of the correlation. coefficient of 0.970 and p-value of 0.001. The five variables influence the work stress of nurses in the inpatient room of the Royal Prima Medan Hospital 2019. The conclusion of this study is that these five variables influence the work stress of nurses in the inpatient room of the Royal Prima Hospital Medan. It is recommended to the hospital to improve the work management system properly.. Keywords: nurse, organizational, individual, work stress